TECHNICAL EFFICIENCY OF PADDY’S FARMING IN VARIOUS TYPES OF PADDY’S SEEDS IN INDONESIA - Venessa Vasthi Winata; M. Rondhi; Yasuhiro Mori; Takumi Kondo (University of Jember, 2020)
The increasing need for food along with increasing population is one of the problems that must be resolved by Indonesia nation. The government is trying to increase rice production and productivity by using certified seeds. Certified seeds is expected to affect technical efficiency of rice farming. The objectives of this studies are to analyze the level of technical efficiency and to identify the factors that influence the technical efficiency of rice farming in various types of main sources of rice seeds in Indonesia. The study uses secondary data that obtained from Central Bureau of Statistic (BPS) as a results from the 2014 Rice Plant Business Household Survey (SPD 2014). Data were analyzed using stochastic frontier. The results showed that the average technical efficiency level achieved by farmers in rice farming is 0,656 or less than 0,70 (<0,70) so it can be said that rice farming in Indonesia is still technically inefficient. Factors that affecting the technical efficiency of rice farming in various types of main sources of rice seeds in Indonesia were age, formal education, dummy participation of agricultural extension, and dummy certified seeds. Keywords: certified seeds, rice farming, stochastic frontier analysis, technical efficiency, non-certified seeds